Thermal modeling of evacuated tube solar air collectors. (May 2015) - Paradis, Pierre-Luc; Rousse, Daniel R.; Hallé, Stéphane; Lamarche, Louis; Quesada, Guillermo
Highlights: Higher is the airflow, better is the efficiency. […] a low airflow can conduct to as much as 100 K of temperature gain. […] the maximum efficiency asymptotically tends to 70%. […] a root mean square error of 0.50 K is calculated on the outlet airflow temperature. Abstract: This paper presents a one dimensional thermal model of a solar evacuated tube open at both ends under transient conditions. Variations of fluid mass flow rate, ambient temperature, solar radiation, and wind speed are accounted for. The semi-analytical model relies on the energy conservation equation for small control volumes along the longitudinal axis of the tube. The first order differential equations obtained for each control volume are solved by use of a fully explicit scheme using a fourth order Runge–Kutta algorithm. An experimental setup has been designed, built and calibrated in order to assess the predictions provided by the model. The comparison between simulated and experimentally measured outlet air temperatures showed a good agreement: a root mean square error on the outlet air temperature of about 0.50 K and a mean bias difference of 0.15 K were observed for experiments conducted on a bright sunny day. The validated model applied for steady state heat transfer is then used to conduct an analysis on different parameters. Finally, the influence of the environmental parameters (solar radiation, ambient temperature and wind speed) and the operating condition (airflow) is investigated on different performance indicators like the outlet air temperature, the efficiency, the mean convective heat transfer coefficient and the pressure drop. It appeared that the influence of wind and ambient temperatures is of minor importance although the influence of solar radiation on the outlet air temperature is significant. Moreover, the airflow is the most important parameter acting on the defined performance indicators. Higher is the airflow, better is the efficiency and lower is the outlet air temperature. On the other hand, a low airflow can conduct to as much as 100 K of temperature gain, but the efficiency is then reduced to value as low as 45%.